Generalized Solutions of the Dirac Equation, W Bosons, and Beta Decay - Andrzej Okniński (Advances in High Energy Physics)
We study the 7×7 Hagen-Hurley equations describing spin 1 particles. We split these equations, in the interacting case, into two Dirac equations with nonstandard solutions. It is argued that these solutions describe decay of a virtual W boson in beta decay.